ASSESSING EFFICIENCY OF THE CONIFEROUS ENERGY SUPPLEMENT IN THE DIET OF DAIRY COWS FOR MAINTAINING PRODUCTIVE HEALTH - Bogolyubova, Nadezhda Vladimirovna; Korotky, Vasily Pavlovich; Zenkin, Alexander Sergeyevich; Romanov, Viktor Nikolaevich; Ryzhov, Viktor Anatolyevich (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: This study was aimed at assessing efficiency of the original coniferous energy supplement in the diet of cows at the end of the dry period - beginning of lactation - for improving the energy density of diets, enriching them with vitamins and major and minor nutrient elements, improving milk productivity, and maintaining productive health. Methods: The scientific-production experiment was performed on the basis of the Lukoshkinoâ€ unit of the Klenovo-Chegodaevoâ€ research farm (Moscow) on twenty cows. The preparation was fed at the rate of 150 g for 20 days before calving and for 30 days after calving. Results: Studies have found the positive effect of the preparation on the average daily milk yield, natural fat content increased by 5.4%-6.9% (with butterfat percentage increased by 0.09%), and reduced cost of feed per unit of obtained product. Conclusion: The use of the preparation promoted enzymatic processes in the rumen, had positive effect on the carbohydrate-lipid and protein metabolism, and had no negative effect on the non-specific resistance of cows.